2015
DOI: 10.1021/acs.bioconjchem.5b00528
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Liposomal MUC1 Glycopeptide-Based Immunotherapeutic and Evaluation of the Effect of l-Rhamnose Targeting on Cellular Immune Responses

Abstract: Generation of a CD8+ response to extracellular antigen requires processing of the antigen by antigen presenting cells (APC) and cross-presentation to CD8+ T cell receptors via MHC class I molecules. Cross-presentation is facilitated by efficient antigen uptake followed by immune-complex-mediated maturation of the APCs. We hypothesize that improved antigen uptake of a glycopeptide sequence containing a CD8+ T cell epitope could be achieved by delivering it on a liposome surface decorated with an immune complex-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 65 publications
1
47
0
Order By: Relevance
“…Recently, Karmakar et al made the L-rhamnose (Rha) epitope-anchored liposomes conjugated with the synthetic TLR2a Pam3Cys-linked glycopeptide Ags derived from MUC1, which is a mucin overexpressed on several types of cancers, and had been engineered to contain a GalNAcα1-Ser/Thr segment to have the immunogenic peptide epitopes exposed to immune system (Fig. 8) [142]. In vivo experiments demonstrated that, administered to the Rha-preimmunized C57BL/6 mice, the Rha epitope-and Ag-anchored liposomes remarkably enhanced production of the MUC1-specific CTLs as well as Abs.…”
Section: Liposomes Engineered With Functional Materials For Constructmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Karmakar et al made the L-rhamnose (Rha) epitope-anchored liposomes conjugated with the synthetic TLR2a Pam3Cys-linked glycopeptide Ags derived from MUC1, which is a mucin overexpressed on several types of cancers, and had been engineered to contain a GalNAcα1-Ser/Thr segment to have the immunogenic peptide epitopes exposed to immune system (Fig. 8) [142]. In vivo experiments demonstrated that, administered to the Rha-preimmunized C57BL/6 mice, the Rha epitope-and Ag-anchored liposomes remarkably enhanced production of the MUC1-specific CTLs as well as Abs.…”
Section: Liposomes Engineered With Functional Materials For Constructmentioning
confidence: 99%
“…Schematic structure the VADS constructed with the Rha epitope-anchored liposomes loaded with Pam3Cys-linked MUC1 glycopeptide Ags, and the principle underlying the immunostimulatory action of the VADS. Reprinted with permission from Reference[142].…”
mentioning
confidence: 99%
“…In recent studies, Karmakar, et al observed improved antigen uptake and cellular response by targeting Fcγ receptors on DCs [ 67 , 68 , 69 ]. The natural abundance of specific natural anti-Rhamnose antibodies in the human population was exploited using L-rhamnose as a targeting ligand [ 70 ].…”
Section: Liposomesmentioning
confidence: 99%
“…With advances in science and technology, the pharmaceutical, health care, and IT industry, accompanied by high-pace shifts in the global economy, bolstered the process of modern-day drug discovery and development to a large significance. Novel interdisciplinary research involving metal and polymer nanoparticles, liposomes, antibodies, and neo-antibiotics in both academia and industries have opened venues for precision diagnosis, targeted drug delivery, and innovative immunotherapy [16][17][18][19][20][21][22][23][24]. Although the classical steps in drug discovery (involving target validation, lead molecule design, chemical synthesis, pre-clinical evaluation, ADME, clinical trials and development for market of the pharmaceutical agents) are followed to date, the distribution of funding at each stage have changed due to the changing global market and healthcare policies [25].…”
Section: Modern-day Fabric Of Pharmaceutical Industrymentioning
confidence: 99%